Inflammasomes in Common Immune-Related Skin Diseases - Tang, Lili; Zhou, Fusheng (Frontiers in Immunology, 2020)
The inflammasome is an important protein complex that cleaves the proinflammatory cytokines pro-IL-1β and pro-IL-18 into their active forms. Owing to its critical role in eliciting innate immune responses, IL-1β has been suggested to contribute to various skin diseases, including psoriasis, vitiligo, systemic lupus erythematosus (SLE), and atopic dermatitis (AD). Recently, several types of activators and inhibitors of different inflammasomes, as well as inflammasome-related genes and genetic susceptibility loci, have been identified in these immune-related common skin diseases. In particular, inflammasome activators and inhibitors presented highly cell-type-specific activity, suggesting that the inflammasome might perform different functions in different cell types. Moreover, most of these findings were based on experimental disease models, and the clinical features of the models partly resemble the typical symptoms of the diseases. In this review, from the perspective of activators and inhibitors, we collected evidence from the widely-studied inflammasomes, NLRP3, AIM2 and NLRP1, in psoriasis, vitiligo, SLE, and AD. Importantly, some small-molecule inhibitors hold therapeutic promise for the treatment of these diseases.